Your brain doesn’t look a day past 70! Cross-sectional associations with brain-predicted age in the cognitively-intact oldest-old - Mark K. Britton; Hannah Hoogerwoerd; Joshua Juhasz; Keyanni Joy Johnson; Paul D. Stewart; Pradyumna K. Bharadwaj; Stacy S. Merritt; Cortney J. Jessup; Clinton B. Wright; G. Alex Hishaw; David A. Raichlen; Victor A. Del Bene; et al. (GeroScience, 2025)
The cognitively-intact oldest-old (85 +) may be the most-resilient members of their birth cohort; due to survivorship effects (e.g., depletion of susceptibles), risk factors associated with brain aging biomarkers in younger samples may not generalize to the cognitively-intact oldest-old. We evaluated associations between established aging-related risk factors and brain-predicted age difference (brainPAD) in a cross-sectional cognitively-intact oldest-old sample. Additionally, we evaluated brainPAD-cognition associations to characterize brain maintenance vs. cognitive reserve in our sample. Oldest-old adults (N = 206; 85–99 years; Montreal Cognitive Assessment > 22 or neurologist evaluation) underwent T1-weighted MRI; brainPAD was generated with brainageR, such that more-positive brainPAD reflected more-advanced brain aging. Sex, education, alcohol and smoking history, exercise history, BMI, cardiovascular and metabolic disease history, and anticholinergic medication burden were self-reported. Global cognitive z-score and coefficient of variation were derived from the UDS 3.0 cognitive battery; crystallized-fluid discrepancy was derived from the NIH Toolbox Cognitive Battery. Mean brainPAD was -7.99 (SD: 5.37; range: -24.50, 6.03). Women showed more-delayed brain aging than men (B = -2.9, 95% CI = -4.6, -1.1, p = 0.002). No other exposures were significantly associated with brainPAD. BrainPAD was not associated with any cognitive variable. These findings suggest that cognitively-intact oldest-old adults may be atypically-resistant to risk factors associated with aging in younger samples, consistent with survivorship effects in aging. Furthermore, brainPAD may have limited explanatory value for cognitive performance in cognitively-intact oldest-old adults, potentially due to high cognitive reserve. Overall, our findings highlight the impact of survivorship effects on brain aging research. Graphical Abstract

Time since HIV diagnosis is linked to amnestic mild cognitive impairment (MCI) in older adults with HIV - Jason S. DeFelice; Mark K. Britton; Yancheng Li; Eric C. Porges; Gladys E. Ibañez; Charurut Somboonwit; Robert L. Cook; Ronald A. Cohen; Joseph M. Gullett (Journal of NeuroVirology, 2025)

Semantic processing in older adults is associated with distributed neural activation which varies by association and abstractness of words - Amanda Garcia; Ronald A. Cohen; Kailey G. Langer; Alexandria G. O’Neal; Eric C. Porges; Adam J. Woods; John B. Williamson (GeroScience, 2024)

Learning ratio performance on a brief visual learning and memory test moderates cognitive training gains in Double Decision task in healthy older adults - Cheshire Hardcastle; Jessica N. Kraft; Hanna K. Hausman; Andrew O’Shea; Alejandro Albizu; Nicole D. Evangelista; Emanuel M. Boutzoukas; Emily J. Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; Eric Porges; et al. (GeroScience, 2024)

The impact of a tDCS and cognitive training intervention on task-based functional connectivity - Jessica N. Kraft; Aprinda Indahlastari; Emanuel M. Boutzoukas; Hanna K. Hausman; Cheshire Hardcastle; Alejandro Albizu; Andrew O’Shea; Nicole D. Evangelista; Emily J. Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; et al. (GeroScience, 2024)

Connecting memory and functional brain networks in older adults: a resting-state fMRI study - Jori L. Waner; Hanna K. Hausman; Jessica N. Kraft; Cheshire Hardcastle; Nicole D. Evangelista; Andrew O’Shea; Alejandro Albizu; Emanuel M. Boutzoukas; Emily J. Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; et al. (GeroScience, 2023)

Task-based functional connectivity of the Useful Field of View (UFOV) fMRI task - Jessica N. Kraft; Hanna K. Hausman; Cheshire Hardcastle; Alejandro Albizu; Andrew O’Shea; Nicole D. Evangelista; Emanuel M. Boutzoukas; Emily J. Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; Steven DeKosky; et al. (GeroScience, 2023)

Higher white matter hyperintensity load adversely affects pre-post proximal cognitive training performance in healthy older adults - Emanuel M. Boutzoukas; Andrew O’Shea; Jessica N. Kraft; Cheshire Hardcastle; Nicole D. Evangelista; Hanna K. Hausman; Alejandro Albizu; Emily J. Van Etten; Pradyumna K. Bharadwaj; Samantha G. Smith; Hyun Song; Eric C. Porges; et al. (GeroScience, 2022)

Proximal improvement and higher-order resting state network change after multidomain cognitive training intervention in healthy older adults - Cheshire Hardcastle; Hanna K. Hausman; Jessica N. Kraft; Alejandro Albizu; Andrew O’Shea; Emanuel M. Boutzoukas; Nicole D. Evangelista; Kailey Langer; Emily J. Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; et al. (GeroScience, 2022)

Cingulo-opercular and frontoparietal control network connectivity and executive functioning in older adults - Hanna K. Hausman; Cheshire Hardcastle; Alejandro Albizu; Jessica N. Kraft; Nicole D. Evangelista; Emanuel M. Boutzoukas; Kailey Langer; Andrew O’Shea; Emily J. Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; et al. (GeroScience, 2022)

Higher-order resting state network association with the useful field of view task in older adults - Cheshire Hardcastle; Hanna K. Hausman; Jessica N. Kraft; Alejandro Albizu; Nicole D. Evangelista; Emanuel M. Boutzoukas; Andrew O’Shea; Kailey Langer; Emily Van Van Etten; Pradyumna K. Bharadwaj; Hyun Song; Samantha G. Smith; et al. (GeroScience, 2022)

Associations of alcohol use, HIV infection, and age with brain white matter microstructure - Mollie A. Monnig; Joseph M. Gullett; Eric C. Porges; Adam J. Woods; Peter M. Monti; Karen Tashima; Neda Jahanshad; Paul Thompson; Talia Nir; Ronald A. Cohen (Journal of NeuroVirology, 2021)

An fMRI study of age-associated changes in basic visual discrimination - Talia R. Seider; Eric C. Porges; Adam J. Woods; Ronald A. Cohen (Brain Imaging and Behavior, 2021)

Effects of propranolol on conversational reciprocity in autism spectrum disorder: a pilot, double-blind, single-dose psychopharmacological challenge study - Rachel M. Zamzow; Bradley J. Ferguson; Janine P. Stichter; Eric C. Porges; Alexandra S. Ragsdale; Morgan L. Lewis; David Q. Beversdorf (Psychopharmacology, 2016)

Age exacerbates HIV-associated white matter abnormalities - Talia R. Seider; Assawin Gongvatana; Adam J. Woods; Huaihou Chen; Eric C. Porges; Tiffany Cummings; Stephen Correia; Karen Tashima; Ronald A. Cohen (Journal of NeuroVirology, 2016)